Determinantal inequalities for J -accretive dissipative matrices - BEBIANO, Natália; DA PROVIDÊNCIA , João (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In this note we determine bounds for the determinant of the sum of two J -accretive dissipative matrices with prescribed spectra. Mathematics Subject Classification (2010): 46C20, 47A12.